The Women of Sparta - Kulesza, Ryszard (Anabasis. Studia Classica et Orientalia, 2013)
In the ancient sources, European tradition and modern-day research, the fabulous Sparta and the historical Sparta coexist, overlapping to the extent that they are often very difficult to tell apart. Spartan women are an important element of both. Scholarly analyses usually present a static image of Spartan women. Yet Sparta itself was changing, and the position, and the image, of its women was undergoing transformations with it. The gradual “mythologisation” of a Spartan woman finally led to her being presented as the epitome of Spartan ideals. The author of the article confronts the images of Spartan women provided by Aristotle, Xenophon and the tragedy and comedy writers with the current state of knowledge regarding the historical Spartan women of the 6 th /5th and 4 th /3 rd century BC. This confrontation shows how the myth of the extraordinary Spartan woman was growing, to reach its ultimate variant in Plutarch, where it finally emerged as the previously unknown, famed image of the “Spartan mother”.